Transcriptome and yeast two-hybrid sequencing shed light on the crosstalk between light and jasmonate signaling in regulating tanshinone biosynthesis - Han Zheng; Xueqing Fu; Muyao Yu; Qi Liu; Chenyi Li; Ling Li; Shuyi Qian; Kang Chen; Shuncang Zhang; Kexuan Tang; Luqi Huang (Medicinal Plant Biology)
As a high-value active component in Salvia miltiorrhiza (Danshen), the accumulation of tanshinones is under the influence of various environmental factors, yet it is unknown whether light, as an essential environmental factor for plant growth, regulates the biosynthesis of tanshinones. In this study, we first measured the temporal accumulation of jasmonates (JAs) and tanshinones under dark-to-light transition, and found that the accumulation of JA, JA-Ile and tanshinones is light-dependent. Transcriptome analysis revealed that SmAOS and SmAOC involved in JA biosynthesis responded rapidly under dark-to-light transition, followed by the accumulation of JA and JA-Ile. A light-responsive transcription factor SmHY5 was filtered indicating a potential regulatory relationship with tanshinone-related genes. Co-expression analysis identified multiple classes of transcription factors highly correlated with JAs and tanshinone biosynthetic genes, among which SmHY5 was confirmed to interact with SmBBX21 through Y2H-seq. Further confirmation of the interaction between SmHY5 and the IV subfamily of SmBBXs, including SmBBX20-24, was obtained through Y2H experiments. Specifically, SmBBX20 and SmBBX21 showed tissue-specific expression in aboveground and underground tissues, consistent with the accumulation sites of JAs and tanshinones. Taken together, this study contributes to the understanding of light and JA signaling in tanshinone biosynthesis in Danshen. We propose a crosstalk between light and JA signaling which regulates tanshinone biosynthesis through the SmHY5-SmBBXs complex and thus provide a basis for improving tanshinone production through the combination of light and JA.